The Influence of Leadership Style and Work Ethic on KSP Employees' Performance. Kopdit Suru Pudi Koting - Handrianto Romilson; Antonius Philippus Kurniawan; Paulus Juru (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to (1) describe employee performance, leadership style, and work ethic; (2) analyze the influence of Leadership Style ad Work Ethics on employee performance either partially or simultaneously. The population in this study were Suru Pudi Koting Credit Union's employees, totaling 30 people. Due to limited population, this research was conducted through census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is done through the F test and t test. The descriptive analysis showed that the variables of employee performance, leadership style, and work ethic were categorized as good. The results of the t-test statistics showed that partially, the leadership style and work ethic had a positive and significant influence on employee performance. The results of the F test statistics revealed that simultaneously, all independent variables had a significant influence on employee performance. The results of the determination analysis showed that the two independent variables in this study were able to explain the fluctuation of employee performance of the Suru Pudi Koting Credit Union as many as 912.7%.